The L-shaped mastopexy - Roberto Luiz Sodré; José Augusto Calil; Renato de Azevedo Ferreira; Paulo Rogério Quieregatto do Espírito Santo; Camila Trigo Ruiz; Marllus Fernando Piotrowsky; Sheila Cover; Maycon Lucas Barbosa (Revista Brasileira de Cirurgia Plástica)
Introduction: The mastopexy with implants and L-shaped scarring aims to correct grades I to II breast ptosis using implants in retroglandular space and retromuscular dual plane space, at the same surgical time. The objective is to describe the experience with the L-augmentation mastopexy technique, analyzing complications and reoperations. Methods: Retrospective study of 123 patients with mild to moderate breast ptosis, operated using the L-augmentation mastopexy technique from January 2011 to November 2021 Results: The mean age of patients was 35.6 years. The average volume of implants used was 315ml (range 175 to 600ml). The placement of the prosthesis was in retroglandular (46.5%) and dual plane retromuscular space (53.5%). The average operative time was two hours and fifty-four minutes. The main complications presented were superficial dehiscence (7.3%), recurrence of ptosis (7.3%) and unsightly scars (5.7%). Surgical reviews took place in 13 patients (10.5%). Conclusion: Safe and effective mastopexy technique with implant in the treatment of mild to moderate breast ptosis, providing well designed breasts with reduced L-shaped scars.